Experimental study of transverse effects in planar dielectric wakefield accelerating structures with elliptical beams - Y. Saveliev; T. J. Overton; T. H. Pacey; N. Joshi; S. Mathisen; B. D. Muratori; N. Thompson; M. P. King; G. Xia (Physical Review Accelerators and Beams, 2022)
The main obstacle to the practical implementation of the dielectric wakefield acceleration (DWA) concept is the development of the beam breakup instability due to transverse dipole wakefields generated when the beam propagates off axis in the accelerating structure. One of the methods to suppress this instability is to elliptically shape the beam and accelerate it in a planar structure. Here, we report a detailed experimental investigation of the transverse dynamics of elliptical beams in planar dielectric structure with parameters mimicking future DWA modules. Both dipole and quadrupole wakefields’ effects on beam stability and projected emittance were studied. This study has highlighted the importance of counteracting quadrupole wakefields in future DWA implementations.